How rival partners compete based on cooperation? - Peng, Tzu-Ju Ann; Yen, Meng-Hsien; Bourne, Mike (Elsevier, 2017)
Prior studies of coopetition have explained the what, how and why of firms cooperating with competitors. Among these, examining the how question as to the stream of coopetition dynamics is the most challenging theme. Previous research has focused much more on the cooperation side. Less attention has been paid to the competition side to reveal what happens to competition after the competitors have collaborated. This study sheds light on the issue of cooperation-based competition by answering the question: while cooperating with competitors, how do rival partners compete based on cooperation? Linking the competitive dynamics perspective to coopetition, we conducted a single-case study to analyse the competition between two leading competitors in the Taiwanese bicycle industry. We collected the reported issues pertaining to the competition in the European market and supported by in-depth interviews. The analysis leads us to develop three propositions and a conceptual framework for illustrating the cooperation-based competition and addressing how cooperation may influence competition in a coopetition relationship. This study provides new insights into a theoretical issue of cooperation-based competition. The case also provides management implications while taking a coopetition strategy.
Keywords: Cooperation; Competitive dynamics; Cooperation-based competition; Bicycle industry